Ear drops for the removal of ear wax. - Burton, M; Dorée, C (2003)
BACKGROUND: Problems attributed to the accumulation of wax (cerumen) are one of the most common reasons for people to present to their general practitioners with ear trouble (Sharp 1990). Treatment for this condition often involves use of a wax softening agent (cerumenolytic) in order to disperse the cerumen and reduce the need for syringing, or to facilitate syringing should it prove necessary, but there is no consensus on the effectiveness of the wide variety of cerumenolytics in use. OBJECTIVES: To assess the effectiveness of ear drops (cerumenolytics) for the removal of symptomatic ear wax. SEARCH STRATEGY: We searched the Cochrane ENT Group Register, the Cochrane Central Register of Controlled Trials (CENTRAL, Issue 1, 2003), and MEDLINE and EMBASE up to March 2003. Reference lists of all trials were also manually searched. SELECTION CRITERIA: We identified all randomised controlled trials (with or without blinding) in which a cerumenolytic was evaluated in comparison with either no treatment, a placebo, or other cerumenolytics in participants with hard or impacted ear wax, and in which the proportion of participants with sufficient clearance of the external canal to make further mechanical clearance unnecessary (primary outcome measure) was stated or calculable. The full text articles of all the retrieved trials of possible relevance were reviewed by the two reviewers and the inclusion criteria applied independently. Any differences in opinion about which studies to include in the review were resolved by discussion. DATA COLLECTION AND ANALYSIS: Trials were graded for methodological quality using the Cochrane approach. Data extraction was performed in a standardised manner by one reviewer and rechecked by the other reviewer, and where necessary investigators were contacted to obtain missing information. Meta-analysis was neither possible nor considered appropriate because of the heterogeneity of the treatments, treatment amounts and durations, trial procedures, and scoring systems. A narrative overview of the results is therefore presented. MAIN RESULTS: Eight trials satisfied the inclusion criteria, the majority of which were of poor quality. In all, 587 participants received one of nine different cerumenolytics. One trial compared active treatments with no treatment, two trials compared active treatments with water or a saline 'placebo', and all eight trials placed two or more active treatments in head-to-head comparisons. Seven trials included syringing as a secondary treatment where necessary.Overall, results were inconclusive. One trial found a significant difference between one of three active agents (Cerumol) in comparison to no treatment, but no statistically significant difference was found between these three agents (sodium bicarbonate ear drops; Cerumol; sterile water). In two trials no statistical difference was found between the effectiveness of either sodium bicarbonate ear drops, Cerumol, Cerumenex or Colace versus a sterile water or saline 'placebo'. Three trials (from the same source) found statistically significant differences in favour of the same active agent (Exterol) in comparison to glycerol and Cerumol. Three trials found no statistically significant difference between two or more cerumenolytics (Otocerol versus Cerumol; Audax versus Earex; sodium bicarbonate ear drops versus Cerumol). Two trials comparing the same two cerumenolytics (Cerumenex versus Colace) also failed to show any significant benefit of one over the other. No serious adverse effects were reported from any of the interventions. REVIEWER'S CONCLUSIONS: Trials to date have been heterogeneous and of poor quality, making it difficult to offer any definitive recommendations on the effectiveness of cerumenolytics for the removal of symptomatic ear wax. Future trials should be of high methodological quality, have large sample sizes, and compare both oil-based and water-based solvents with placebo and/or no treatment.